Assessment of Knowledge and Performance Regarding Triage Among Nurses Working in Emergency Unit-Al Dawadmi General Hospital: A Cross Sectional Study - Walaa Ahmad Eisa1 , Awatif Alhmeidi Alenizi2 , Entesar-makhlouf3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Five experts validated the contents of the tools and tested for reliability, using Cronbach’s alpha, thetool correlation coefficient was 0.79. The majority of participants (74.46%) were in the age group of <30 years. More than half of the studied subjects (59.57) are male. The majority of them have BSc andabout 70.21% work experience for more than five years. Only 72.34% of them had not attended any formof workshops about Triage. 70.2% of them knowing the purpose of triage, 91.2 % know color used innonurgent situations, while 91.5% not know the time of Triage.93.6% of them not know the importance ofurine analysis in the triage unit. The majority of them (80.90 %) strongly agree that hospital Triage is good.knowledge about triage is a key in triage decision making. The study findings revealed that there were stilldeficits in the triaging knowledge and skills of nurses.